2023
DOI: 10.1001/jamainternmed.2023.0629
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Coaching Intervention to Improve Cardiologist Communication

Abstract: ImportanceCommunication between cardiologists and patients can significantly affect patient comprehension, adherence, and satisfaction. To our knowledge, a coaching intervention to improve cardiologist communication has not been tested.ObjectiveTo evaluate the effect of a communication coaching intervention to teach evidence-based communication skills to cardiologists.Design, Setting, and ParticipantsThis 2-arm randomized clinical trial was performed at outpatient cardiology clinics at an academic medical cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“… 13 And a randomized trial that evaluated a coaching intervention in which coaches taught 5 different communication skills to cardiologists revealed that those who received coaching had improved their ability to express empathy and elicit questions from patients. 9 Overall, these studies and others illustrate that communication skills can be improved through explicit instruction. 14 But one scoping review that assessed 151 articles on communication skills training programs concluded that many programs lacked curriculum structure, focus, and standardization, and the authors recommended a more rigorous approach to program development.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“… 13 And a randomized trial that evaluated a coaching intervention in which coaches taught 5 different communication skills to cardiologists revealed that those who received coaching had improved their ability to express empathy and elicit questions from patients. 9 Overall, these studies and others illustrate that communication skills can be improved through explicit instruction. 14 But one scoping review that assessed 151 articles on communication skills training programs concluded that many programs lacked curriculum structure, focus, and standardization, and the authors recommended a more rigorous approach to program development.…”
Section: Introductionmentioning
confidence: 82%
“…Thus, a wide range of approaches, frameworks, and curriculums have been developed to help health care professionals at any career stage learn a range of communication strategies. 6 13 For instance, surgery residents who took an 8-module training that covered empathic communication, end-of-life conversations, bad news delivery, and medical error disclosure reported positive learning experiences and increased confidence—results that correlated with patient perceptions of improved surgeon communication. 13 And a randomized trial that evaluated a coaching intervention in which coaches taught 5 different communication skills to cardiologists revealed that those who received coaching had improved their ability to express empathy and elicit questions from patients.…”
Section: Introductionmentioning
confidence: 99%
“…Training programs that teach clinicians the language of empathy may be a solution . However, given that the detection of emotion in others and empathic reactions are racialized, it is necessary to confirm whether the benefits of such training programs are experienced by all patients and caregivers . Further, communication training typically only focuses on managing negative emotions, which may be preferentially responsive to one specific sociocultural norm of communication.…”
Section: Discussionmentioning
confidence: 99%
“…We randomly selected 35 recordings from a larger intervention, randomized control trial [ 20 ]. We qualitatively coded these audio recordings ( n = 20 female, 15 male; Mage = 59.27, SD = 15.97; 66% had a bachelor's degree or higher) and their corresponding transcriptions of both white patient ( n = 13), white cardiologist interactions and Black patient ( n = 22), white cardiologist interactions in an academic medical center.…”
Section: Methodsmentioning
confidence: 99%